Multi‐sensor data fusion between radio tomographic imaging and noise radar. Issue 2 (1st February 2020) - Vergara, Christopher; Martin, Richard K.; Collins, Peter J.; Lievsay, James R.
Abstract : Radio tomographic imaging and noise radar are two proven surveillance technologies. The novelty of fusing data from radio tomographic imaging and noise radar is achieved with the derivation of a fusion technique utilising Tikhonov regularisation. Analysing the results of the Tikhonov influenced techniques reveals an average 43–47% error decrease in target centroid location, a 13–19% size decreases in target pixel dispersion and a 6–41% improvement in an ideal solution comparison. Results provide the radio tomographic imaging and noise radar communities a proof of concept for the fusion of data from two disparate sensor technologies.